Spatial variability in soil chemical properties under Dactyladenia barteri, Alchomea cordifolia, Senna siamea, and Gmelina arborea hedgerows on an acid Ultisol - Ruhigwa, B.; Gichuru, M.; Tariah, N.; Isirimah, N.; Douglas, D. (Cambridge University Press, 1993)
Spatial nutrient distribution was studied under a three-and-a-half-year-old fallow of Dactyladenia barteri, Alchornea cordifolia, Senna siamea and Gmelina arborea hedgerows grown on an acid Ultisol in southeastern Nigeria. The objectives were to evaluate the nutrient cycling capacity and suitability of the hedgerow species for alley cropping. No consistent patterns were observed in the lateral distribution of soil pH, total nitrogen, organic carbon, available phosphorus, exchangeable cations (potassium, calcium, magnesium and sodium), total acidity and effective cation exchange capacity in the 4 m wide alleys formed between the hedgerow species. Senna siamea and Gmelina arborea tended to increase soil organic carbon, calcium, magnesium and effective cation exchange capacity, particularly in the top 50 cm, compared with Alchornea cordifolia and Dactyladenia barteri, and can therefore be recommended for soil fertility regeneration on acid Ultisols during periods of fallow. However, they appear to be less suitable for alley cropping than Dactyladenia barteri because they are shallow rooting.